THE CITIZEN CENTRIC APPROACH IN THE IMPLEMENTATION OF E-GOVERNMENT AS AN EFFORT TO IMPROVE THE QUALITY OF PUBLIC SERVICES IN THE GOVERNMENT OF WEST JAVA PROVINCE - Muhammad Fauzi; Yogi Suprayogi Sugandi; Deden Hadi Kushendar (Jurnal Ekonomi, 2023)
To enhance public services and governance in West Java, the province government may have implemented a number of e-Government initiatives. West Java has built Public Service Centers to provide integrated services and a one-stop shop for citizens, and the government of West Java has adopted the idea of citizen-centric governance to prioritize its citizens' needs, aspirations, and well-being. Sapawarga is an innovative e-government initiative implemented in West Java Province, Indonesia. Adopting a citizen-centric approach in the implementation of e-government can greatly contribute to improving the quality of public services. The implementation of digital services in West Java, Indonesia has had several positive effects on citizens. A citizen-centric approach includes a number of components, including user-centered design, service personalization, multichannel service delivery, transparent information, citizen feedback channels, and continual improvement. The Government of West Java Province's ability to provide high-quality public services can be greatly enhanced by using a citizen-centric approach to implementation.